Spectrum of primary epithelial tumors of major salivary glands: a 5 year record based descriptive study from a tertiary care centre - Leelamma, Jayalakshmy Payippat; Mohan, Bhavya P. (International Journal of Advances in Medicine, 2017)
Background: Salivary gland tumors constitute a highly heterogeneous histopathologic group. There are few epidemiological studies of large series of benign and malignant epithelial tumors of major salivary glands in South India. Methods: This is a retrospective study in a tertiary care centre in Kerala, South India. A total of 180 epithelial neoplasms of major salivary gland were studied over a 5 year period. In each case age, sex, anatomical location and histopathological diagnosis were recorded. Results: Patients with benign and malignant tumors presented with a mean age of 52.3 and 55.9 years respectively. The frequency of benign tumors was 80.6% (n = 145) and of malignant tumors was 19.4% (n = 35). There was a higher prevalence of tumors in males 60.6% (n = 109) than in females 39.4% (n = 71). 91.9% (n = 164) of the tumors were localized in the parotid gland, 8.3% (n = 15) in the submandibular gland and 0.6% (n = 1) in the sublingual gland. The most common benign tumors were Pleomorphic adenoma (48.9%, n = 88) and Warthin’s tumor (28.9%, n = 52). Among malignant tumors, Mucoepidermoid carcinoma was the most common (9.5%, n = 17) followed by Carcinoma ex pleomorphic adenoma (2.8%, n = 5) and adenoid cystic carcinoma (2.2%, n = 4). Conclusions: Parotid gland was the most common site of both benign and malignant tumours. Plemorphic adenoma was the most common benign tumor and mucoepidermoid carcinoma was the most common malignant tumor.